2019
DOI: 10.1007/s00213-019-05292-2
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic drug treatment remediates exaggerated cingulate prediction error responses in obsessive-compulsive disorder

Abstract: Rationale Patients with obsessive-compulsive disorder (OCD) have been found to show exaggerated error responses and prediction error learning signals in a variety of EEG and fMRI tasks, with data converging on the anterior cingulate cortex as a key locus of dysfunction. Considerable evidence has linked prediction error processing to dopaminergic function. Objective In this study, we investigate potential dopaminergic dysfunction during reward processing in the context o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 69 publications
(100 reference statements)
1
32
0
Order By: Relevance
“…The healthy volunteer assay we employed has been widely used, is well-validated, and has been shown to be sensitive to and specific for pharmacological manipulations using conventional antidepressants [ 15 ]. In contrast to previous studies on various cognitive effects of pramipexole (e.g., [ 13 , 35 , 36 , 37 , 38 , 39 , 40 ]), we used a subacute, rather than an acute dosing scheme including a comparatively high target dose. Compared to a single-dose challenge, subacute pramipexole treatment has higher clinical-ecological validity—especially considering that acute versus subacute dopaminergic challenges likely differ in their neuromolecular effects [ 8 , 10 , 16 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The healthy volunteer assay we employed has been widely used, is well-validated, and has been shown to be sensitive to and specific for pharmacological manipulations using conventional antidepressants [ 15 ]. In contrast to previous studies on various cognitive effects of pramipexole (e.g., [ 13 , 35 , 36 , 37 , 38 , 39 , 40 ]), we used a subacute, rather than an acute dosing scheme including a comparatively high target dose. Compared to a single-dose challenge, subacute pramipexole treatment has higher clinical-ecological validity—especially considering that acute versus subacute dopaminergic challenges likely differ in their neuromolecular effects [ 8 , 10 , 16 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using probabilistic learning tasks have demonstrated increased prediction error-related activation in the ACC (122,127) and right putamen (122) during the omission of expected reward, while the unexpected receipt of reward has been associated with increased activity in the nucleus accumbens of patients (127). Studies on performance monitoring in OCD patients have also consistently shown enhanced amplitudes of the ERN during the commission of errors [see (13)], which may also be considered as aversive, negative stimuli or events.…”
Section: Emotion Experiencementioning
confidence: 91%
“…In addition, a pharmacological fMRI study of RL has shown an abnormally increased signaling of prediction errors in the anterior ACC. This effect was reduced by both a D 2/3 agonist and an antagonist (30). Modeling results did not demonstrate the same effects but did show a marginally significant reduction in prediction error learning rates in OCD patients (30).…”
Section: Co-morbidity and Trans-dimensional Analysismentioning
confidence: 84%
“…This effect was reduced by both a D 2/3 agonist and an antagonist (30). Modeling results did not demonstrate the same effects but did show a marginally significant reduction in prediction error learning rates in OCD patients (30).…”
Section: Co-morbidity and Trans-dimensional Analysismentioning
confidence: 84%
See 1 more Smart Citation